Isolation of Compounds from the Aqueous Methanol Extract of Cissus javana DC Leaves and Determination of Its Trace Element Content through Wet Digestion - Bimola Devi Asem; Warjeet Singh Laitonjam; Ibopishak Singh Oinam; T. H. Jeena (Current Advances in Chemistry and Biochemistry Vol. 5, 2021)
A new alcohol was isolated from the aqueous methanol extract of the leaves of Cissus javana DC which is widely used in Manipur, India for dissolution and expulsion of kidney stones. In addition, known compounds Stigmasterol, Stigmasterol glucoside, Onocer-7-ene 3\(α\),21\(β\)-diol, \(β\)-amyrin-[olean12(13)-en-3-one] were also isolated from the same methanol extract. Analysis of trace element contents of the plant leaf reflects its role in the ethno medicinal property of the plant. It was found that the plant leaf have exceptionally high calcium (2960 mg/100 g), magnesium (465 mg/100 g) and iron (520 mg/100 g) content.